Drug testing and social control: implications for state theory - Gerber, Jurg (Contemporary crises, 1990)
A new War on Drugs became the rallying cry during the 1986 Congressional elections. One of the major components of this war was the call for mandatory drug testing of workers. We argue that drug testing has more to do with power than with genuine efforts at reducing the consumption of illicit drugs and then proceed to analyze this expansion of power by capitalists and state managers. Contrary to Block's version of state theory, the power of capitalists and state managers expanded simultaneously. We thus conclude by calling for a partial modification of his model.